Effect of Brown Rice and Oyster Mushrooms Food Formulation on Blood Sugar and Lipid Profiles of Diabetics - Kristianto, Yohanes; Sulistyowati, Etik; Sofiani, Siska Dwi (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Foods play an important role in managing diabetes. Brown rice and oyster mushrooms are prospective foods for diabetics due to their low glycemic index and high b-glucan content respectively. This study aimed to determine the impact of food for special dietary use (FSDU) developed with brown rice and oyster mushrooms on the blood sugar and lipid profile of diabetics. The research was conducted using a quasi-experimental design on purposively selected 32 subjects. The subjects were equally assigned into one group receiving the FSDU and the other for commercial formula. The energy and nutrient intakes, blood sugar, and lipid profile were then compared. The results showed that most subjects were female, over 50 years old, and had been living with diabetes for more than five years. The energy intake of the FSDU group and the commercial formula was not significantly different (p > 0.05). However, the FSDU group had higher intakes of protein, carbohydrates, fiber, magnesium, and sodium than those of the commercial group (p < 0.05). Brown rice and oyster mushrooms contributed significantly to fiber intake. Blood glucose levels decreased insignificantly, while LDL increased significantly in the FSDU group. The fasting blood glucose, 2-hour post-prandial blood glucose, HbA1C, and HDL levels of the groups after treatment were not statistically different (p > 0.05). The FSDU formula could be proposed as an alternative to commercial products with the advantage of better nutrient content.